Arbitrary Death: An Empirical Study of Mitigation - Emily Hughes (Washington University Law Review, 2012)
The Supreme Court has long viewed mitigation evidence as key to saving the death penalty from constitutional challenge. Mitigation evidence about a capital defendant’s life history, combined with other procedural protections, is thought to alleviate arbitrariness in juries’ decisions of whether a defendant deserves to die. This Article presents original empirical research studying that hypothesis. Interviews with thirty mitigation specialists who have represented over 700 capital clients in twenty-five death penalty states reveal that despite the Supreme Court’s hope, mitigation evidence has not alleviated arbitrariness in death penalty decisions. Instead, new arbitrariness enters the system through the process of gathering mitigation evidence and presenting it to juries. This Article therefore concludes that mitigation must be reformed if it is to succeed in eliminating arbitrariness in capital punishment decisions. Without such reform, the death penalty will remain unconstitutionally arbitrary despite mitigation.
Keywords: Furman v. Georgia 408 U.S. 238 (1972); Capital punishment; Extenuating circumstances; Judicial discretion; States; United States